Rancang Bangun Tungku Gasifikasi Tipe Downdraft Continue Bahan Bakar Sekam Padi - Khoiri, Muhammad Raisul (2016)
One way to convert biogas into energy that is ready to use is the gasification method. The goal is to get the downdraft gasification stove design, to get to ignite the furnace time, the temperature of the flame and the calorific value that can be produce from downdraft gasification stove. This reseach uses downdraft gasification reactor types which that where the gasification gas flow and air are one way direction that is downward. The study began with designing and building a gasification stove downdraft tipe, then make a test or experiment the continuously of the gasification stove. It was also taken time data Ignition stove, temperature, and the value of the heat produced. The results showed that the furnace gasification type downdraft continue with a diameter of 170 mm, height 650 mm, throat angle 600, with rice husk as fuel is capable of burning at minute 10 with highest temperature 5730C, burning for 36 minutes with a calorific value of boiling water by 2626, 7 kJ. And the furnace is refilled capable of burning rice husk at minute 6 with the highest temperature 5730C, burning for 62 minutes and has a calorific value of 4369.2 kJ.